2020
DOI: 10.1177/1934578x20936931
|View full text |Cite
|
Sign up to set email alerts
|

Total Polyphenol Content, Antioxidant Activity, and Individual Phenolic Composition of Different Edible Parts of 4 Sweet Potato Cultivars

Abstract: The quest to determine and use polyphenolic compounds present in fruits and vegetables as natural antioxidants has recently attracted much attention due to their beneficial health effects. In this study, the total polyphenol content (TPC), total flavonoid content (TFC), total anthocyanin content (TAC), antioxidant activity (AA), and individual polyphenol components of Simon No. 1, Yuzi No. 7, Shangshu 19, and Pushu 32 sweet potato cultivars (edible parts: leaf, stalk, stem, skin, and flesh) were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
(64 reference statements)
4
17
1
Order By: Relevance
“…On the other hand, in sweet potato ( Ipomoea batata L . ), 3,5-O-dicaffeoylquinic acid, astragalin, and cyanidin have been reported as the most abundant phenolic compounds in leaves and flesh, respectively [ 27 ], whereas the concentrations of total anthocyanins are comparable to the reported for colored genotypes from Ecuadorian Andean region were concentrations between 2.74 and 172.53 ug g −1 FW had been reported [ 28 ]. Although that higher concentrations of the phenolic compound have been detected in potato flesh, it has been reported that approximately 50% of these molecules are located in the peel and adjacent sections, including hydroxycinnamic and hydroxybenzoic acids and also non-anthocyanin flavonoids as flavonols and flavan-3-ols, among others [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, in sweet potato ( Ipomoea batata L . ), 3,5-O-dicaffeoylquinic acid, astragalin, and cyanidin have been reported as the most abundant phenolic compounds in leaves and flesh, respectively [ 27 ], whereas the concentrations of total anthocyanins are comparable to the reported for colored genotypes from Ecuadorian Andean region were concentrations between 2.74 and 172.53 ug g −1 FW had been reported [ 28 ]. Although that higher concentrations of the phenolic compound have been detected in potato flesh, it has been reported that approximately 50% of these molecules are located in the peel and adjacent sections, including hydroxycinnamic and hydroxybenzoic acids and also non-anthocyanin flavonoids as flavonols and flavan-3-ols, among others [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 97%
“…Unlike spinach, cabbage, broccoli or kale, sweet potato leaves contain more polyphenols (4). Sweet potatoes high in polyphenol content are increasingly popular with healthconscious consumers (5). Sweet potato leaves, therefore, greatly contribute to the availability of food as well as bioactive compounds for consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Parts of the sweet potato ( Ipomea batatas ), such as the roots, stems, and leaves, are a good source for various compounds: vitamins, essential amino acids, natural antioxidants. However, the amount of bioactive compounds is dependent on their cultivar color and environmental and processing conditions [ 19 ]. Huang et al [ 20 ] found that the phytochemicals present in sweet potatoes have a significant effect on antioxidant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%